Analytical treatment of the couple stress fluid-filled thin elastic tubes - Hashemi, Mir Sajjad; İnç, Mustafa; Akgul, Ali (Elsevier Gmbh, 2017)
In this paper, we present the symmetries and self-adjointness of the problem about the couple stress fluid-filled thin elastic tubes. Some soliton solutions of the specified problem are constructed with the aid of Lie group symmetry method. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Lie group symmetry; Self-adjointness; Soliton